Time resolved effect of heat dispersion on magnetic stability in ferromagnetic ising thin-films: Monte carlo simulation - Laosiritaworn W. (The Korean Magnestics Society, 2015)
In this work, Monte Carlo simulation was used to investigate the magnetization properties of thin ferromagnetic films under a perturbation from a supplied heat pulse on one surface of the films. The finite difference method was used to extract the local temperature of each layer of the films as a function of time for various heat source power and heating period. Then, with the variation of the films temperature, Metropolis method was used to update the magnetic moment in magnetic grain, under the Ising framework and using the FePt parameters. With the extracted magnetization profiles, the relationship between magnetization relaxation in accordance with relevant heat parameters and films thickness was reported and discussed, with a purpose to form a database for future use. © The Korean Magnetics Society. All rights reserved.